(Samo)percepcije mladih v polju političnega - Hrženjak, Majda (Annales. Series historia et sociologia, 2016)
The article addresses the issue of low political participation of the young due to their changed position of being socially redundant, and as a consequence of processes of privatization and commodification of citizenship. These processes are reflected through shifts in the understanding of citizenship and its transition from dutiful to self-actualizing citizenship, through the impact of new communication technologies changing civic practice and through the responses of the young and of political actors to these changes. The authors depart from the three-part analysis of the empirical material collected with interviews with young people and representatives of political parties, and they analyse: how young people perceive their own position in society and structural inequality as a political problem; how political parties understand the participation and citizenship of young people and how they address young people; how young people perceive online communication of political actors. While the interviews confirm the trends of commodification of citizenship, they at the same time confirm that the thesis about the young being apolitical is overrated and a too simplified explanation for the behaviours of the young. Pragmatism of political parties that understand the young primarily as an electoral base and their citizenship primarily as a practice of duty is reflected by the young critically as alienation of institutional policy, which does not recognize the political potential to directly and effectively address the problems which affect society in general and the young specifically. Increasing the involvement of young people in active citizenship, therefore, requires a more complex reading of participation, which is not content with data on voter turnout among young people, but tries to understand the situation of the young, their needs and aspirations, and their situated placement in the political field.
Keywords: dolžnostnostno državljanstvo; državljani; državljanstvo; election; komodifikacija državljanstva; mladi; mladina; participacija; political party; politics; politična angažiranost; politične stranke; politični nazori; politika; Slovenia; Slovenija; volilci; volitve